2020
DOI: 10.1080/02656736.2020.1736649
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-guided percutaneous microwave ablation with artificial ascites for problematic hepatocellular tumors

Abstract: 2020)Computed tomography-guided percutaneous microwave ablation with artificial ascites for ABSTRACT Background: The aim of this study was to assess the feasibility, safety and efficacy of computed tomography (CT)-guided percutaneous microwave ablation with artificial ascites for problematic hepatocellular tumors. Methods: Forty-eight patients with 61 problematic hepatocellular carcinomas who underwent CTguided percutaneous microwave ablation with artificial ascites were reviewed retrospectively. Lesions less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Considering the high risk of thermal injury to the diaphragm around the tumor after MWA, precautionary measures should be taken to avoid collateral damage to adjacent organs. Results of a previous study suggested that the establishment of artificial ascites and/or pleural effusion was equivalent to the formation of a barrier zone, which may separate the adjacent blood vessels, liver and diaphragm from thermal ablation (12)(13)(14). The barrier zone may reduce heat energy conduction and avoid thermal injury, thereby protecting the diaphragm, lung tissues and its internal blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high risk of thermal injury to the diaphragm around the tumor after MWA, precautionary measures should be taken to avoid collateral damage to adjacent organs. Results of a previous study suggested that the establishment of artificial ascites and/or pleural effusion was equivalent to the formation of a barrier zone, which may separate the adjacent blood vessels, liver and diaphragm from thermal ablation (12)(13)(14). The barrier zone may reduce heat energy conduction and avoid thermal injury, thereby protecting the diaphragm, lung tissues and its internal blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with normal saline, hydrodissection with 5% dextrose in water is more protective from adjacent organ injury in radiofrequency ablation; however, either 5% dextrose or normal saline can be used during microwave ablation. 68 69 Faintly radiopaque contrast (2% solution of iodinated contrast in normal saline) is used to aid in the visualization of at-risk anatomy during hydrodissection. While the attenuation difference between hydrodissection fluid and nontarget anatomy is optimized with this technique, there is potential for masking visualization of bleeding given similar densities of acute blood products and dilute contrast.…”
Section: Procedural Detailsmentioning
confidence: 99%
“…At present, there are X-ray, ultrasound, magnetic resonance imaging (MRI), and computed tomography (CT) for the clinical diagnosis of ascites. X-ray and ultrasound have poor diagnostic effect on ascites and cannot make a definite diagnosis [ 12 ]. Although ordinary CT can detect the occurrence of ascites with high resolution, it cannot judge the nature of ascites.…”
Section: Introductionmentioning
confidence: 99%